Women’s associations in Cotopaxi, Ecuador: from rights to agroecological markets - Borja, R.; Blare, T.; Reimão, M.; Padilla, G.; Oyarzún, P. (Informa UK Limited, 2024)
Smallholder, indigenous farmers play a key role in the food system in Ecuador, applying traditional farming practices that ensure the sustainability of their food production and meeting the dietary demands of many urban consumers, especially for organic vegetables and dairy products. This study examines the position of six women’s associations in the central Ecuadorian Andes, discussing their evolution from rights-based to market-oriented organizations producing and selling agroecological products. We discuss how the history of these associations has led them to play a role in local politics and national policies around agriculture and highlight how these organizations have succeeded both economically and socially, while also noting the challenges they face, as observed by themselves and outsiders. While the history of women’s agroecological production organizations in Ecuador may be unique, as it is entrenched in indigenous rights movements, our results also point to opportunities and obstacles that are more common across small scale farmers and deserve attention from both policymakers and agricultural organizations.